2012
DOI: 10.1371/journal.pone.0045281
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal qPCR Study of the Dynamics of L. crispatus, L. iners, A. vaginae, (Sialidase Positive) G. vaginalis, and P. bivia in the Vagina

Abstract: BackgroundTo obtain more detailed understanding of the causes of disturbance of the vaginal microflora (VMF), a longitudinal study was carried out for 17 women during two menstrual cycles.MethodsVaginal swabs were obtained daily from 17 non-pregnant, menarchal volunteers. For each woman, Gram stains were scored, the quantitative changes of 5 key vaginal species, i.e. Atopobium vaginae, Lactobacillus crispatus, L. iners, (sialidase positive) Gardnerella vaginalis and Prevotella bivia were quantified with qPCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 58 publications
3
64
0
Order By: Relevance
“…L. iners also resisted the displacement induced by both G. vaginalis in higher extent that L. crispatus , suggesting that L. iners is more adaptable to cohabitate with BV associated G. vaginalis strains. Previously, the detection of L. iners in women with and recovering from BV has led to the suggestion that this lactobacilli species was not protective against disease 27-29. Our results suggest that L. iners can enhance specific strains of G. vaginalis and could be potentially capable to facilitate the development of BV.…”
Section: Resultsmentioning
confidence: 60%
“…L. iners also resisted the displacement induced by both G. vaginalis in higher extent that L. crispatus , suggesting that L. iners is more adaptable to cohabitate with BV associated G. vaginalis strains. Previously, the detection of L. iners in women with and recovering from BV has led to the suggestion that this lactobacilli species was not protective against disease 27-29. Our results suggest that L. iners can enhance specific strains of G. vaginalis and could be potentially capable to facilitate the development of BV.…”
Section: Resultsmentioning
confidence: 60%
“…Studies also consistently suggest that menses is the largest disturbing factor during the menstrual cycle, with sometimes large reductions in lactobacilli [38], [59], [62], [63], shifts from L. crispatus to L. iners [38], [70], or the appearance of BV-associated bacteria, streptococci or other Gram-positive cocci [54], [70]. Pregnancy, which is also accompanied by high estradiol levels, is associated with high levels of lactobacilli, particularly L. crispatus , and low bacterial diversity [55], [68].…”
Section: Resultsmentioning
confidence: 96%
“…Two important areas of consensus emerged. First, almost all women carry vaginal lactobacilli regardless of their BV status by Nugent or Amsel criteria [19], [20], [22], [23], [25], [26], [33], [37][42], [45], [47], [48], [54], [59], [60], [62], [63], [73], [76], [80] but L. crispatus is predominantly found in BV-negative women [20], [22], [23], [25], [32], [33], [37], [38], [40], [42], [48], [50], [54], [59], [60], [62], [63], [65], [73], [75], [76], [80] whereas L. iners (and to a lesser extent L. gasseri ) is also found in women with intermediate microbiota or BV [21], [23], [25], [33], [37], [38], [40][42], [47], [50], [54], [59], [60], [62], [63], [65], [73], [76], …”
Section: Resultsmentioning
confidence: 99%
“…In this study, L. crispatus showed good inhibition activity on hyphal formation ( Figures 4 , 5 ). Longitudinal studies have also shown that the presence of L. crispatus promoted stability of the vaginal microbiota toward a healthy status (Verstraelen et al, 2009; Santiago et al, 2012). Our findings of L. crispatus strains with generally high inhibition activities on Candida growth and yeast-to-hyphae transition is very attractive.…”
Section: Discussionmentioning
confidence: 99%